Smokeless Tobacco Use, Cigarette Smoking, and Upper Aerodigestive Tract Cancers: A Case-Control Study in the Batna Region, Algeria, 2008-2011. (February 2020) - Oudjehih, Messaouda; Deltour, Isabelle; Bouhidel, Mohamed Larbi; Bouhidel, Atika; Marref, Abdelwahab; Luzon, Véronique; Schüz, Joachim; Bouneceur, Hocine; Leon, Maria E
Background: A significant proportion of the Algerian population uses tobacco products and is at risk of developing tobacco-associated cancers. Aims: This case-control study reports on the association between tobacco use and the occurrence of upper aerodigestive tract (UADT) cancers in Batna, Algeria. Methods: Incident primary UADT cancer cases in residents of Batna in 2008-2011 were identified using the regional tumor registry. One hospital and 1 population control were matched to each case by sex, year of birth, and residence. Information on tobacco use was collected, and odds ratios (ORs) were obtained using conditional logistic regression also after sex stratification. Results: The study included 192 cases (80%) of the 241 primary UADT cancer cases identified and 384 controls. Males represented 76.6% of cancer cases. Cancers of the nasopharynx (48%) and the larynx (26%) were the most common types. Ever use of smokeless tobacco (ST) (OR = 1.0; 95% confidence interval [CI]: 0.6-1.5) or current ST use (OR = 1.1; 95% CI: 0.6-1.7) was not associated with overall risk of UADT cancers. Associations with cancers of the nasopharynx (OR = 1.5; 95% CI: 0.5-4.6) and oral cavity/oropharynx (OR = 3.0; 95% CI: 0.8-11.8) were found when comparing use of ST only to no consumption of any tobacco. Cigarette smoking was associated with an increase in the overall risk of UADT cancers, with a 3-fold increase in the risk of laryngeal cancer when comparing smoking only to no consumption of any tobacco (OR = 3.3; 95% CI: 1.0-11.5). Associations for smokers who also consumed ST differed by cancer site. Conclusion: In this study from Algeria dominated by male cases and by cancer in the nasopharynx, cigarette smoking but not ST was associated with UADT cancer. Analyses by anatomical site and using as reference never use of any type of tobacco suggested few associations with ST but of lower precision.